Pengaruh Ukuran Kap, Ukuran Perusahaan, dan Profitabilitas Perusahaan Terhadap Auditor Switching(Studi Empiris Perusahaan Manufaktur Terdaftar di Bursa Efek Indonesia Periode2009-2014) - Shaputro, Ashari Faudzan; , Drs. Agus Endro Suwarno, M.Si (2016)
This study aimed to examine the effect of the size of public accounting firm, firm size and profitability of the company to the auditor switching on manufacturing companies listed in Indonesia Stock Exchange 2009-2014 period. The variables used in this study is the size of public accounting firm, company size, company profitability, and auditor switching. The population of the sample is manufacturing companies listed in Indonesia Stock Exchange 2009-2014 period. Samples were determined using purposive sampling method. The study had 90 samples from 15 companies. Data analysis technique used is the logistic regression analysis. The results of this study indicate that the size of public accounting firm does not affect the auditor switching with a significance level (α) 0.490 > 0.05, the first hypothesis is rejected. Firm size affect the auditor switching with a significance level (α) 0.034 < 0.05, the second hypothesis is accepted. The company's profitability does not affect the auditor switching with a significance level (α) 0.487 > 0.05, the third hypothesis is rejected.